Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Mengikuti Pendidikan Magister Akuntansi - Wardayanti, Ni Ketut; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2021)
Master of Accounting is a secondary education in higher education to get a master’s degree. This study aims to obtain empirical evidence of the effect of motivation, accreditation of study program, labor market considerations and peer environment status on intention to take master in accounting. The research was conducted at The Faculty of Economics and Business. The sampling technique use was purposive sampling and obtained a sample of 168 samples. Data were analyzed using multiple linear regression analysis. The result of this study indicate that motivation and peer environment status has a positive effect on intention of students to take Master of Accounting Education, while accreditation of study program and labor market considerations has no effect on the interest of student attending the master of Accounting Education. Keywords: Motivation; Accreditation Of Study Program; Labor Market Considerations; Peer Status; Student Interest.